Analysis of microbial community diversity of muscadine grape skins. (July 2021) - Sun, Dayun; Qu, Junjie; Huang, Yu; Lu, Jiang; Yin, Ling
Graphical abstract: Highlights: The microbial community in muscadine grape skins from different cultivars was affected by the grapevine genotype. The cultivar had a greater impact on the fungal community than that of bacteria. At the genus level, the microbial composition of muscadine grape was distinct from that of wine grapes. There were complex interactions among microbial communities. Abstract: Microorganisms in grape skins play vital roles in grapevine health, productivity, wine quality and organoleptic properties. To investigate microbial diversity of muscadine grape skins, 16S and ITS sequences of 30 samples from six muscadine ( Muscadinia rotundifolia Michx.) cultivars grown in Guangxi, China, were sequenced using Illumina Novaseq platform. A total of 7, 317 bacterial operational taxonomic units (OTUs) and 1, 611 fungal OTUs were obtained, and clustered into 38 bacterial and 7 known fungal phyla. The dominant bacterial phyla were Proteobacteria, Firmicutes, Bacteroidetes, Planctomycetes, Actinobacteria, Verrucomicrobia, Acidobacteria, and Patescibacteria, and the dominant genera were Lelliottia, Prevotella _ 9, Escherichia - Shigella, Lactobacillus, Pseudomonas, Akkermansia, Faecalibacterium, Rahnella, and Acinetobacter . For fungi, the dominant phyla were Ascomycota, Basidiomycota, and Mortierellomycota, and the dominant genera were Acaromyces, Uwebraunia, Penicillium, Zygosporium, Ilyonectria, Aspergillus, Neodevriesia, Strelitziana, Mortierella, and Fusarium . Alpha diversity analysis and Kruskal-Wallis H test demonstrated that microbial diversity and composition were affected by the cultivar. The Pearson correlation analysis of species revealed complex interactions among microbes. PICRUSt2 predicted that the metabolism of carbohydrates, cofactors, vitamins, amino acids, terpenoids, polyketides, lipids and biosynthesis of other secondary metabolites were abundant. These results contribute to understanding the uniqueness of muscadine grapes and the links among microorganisms in grape skins.